Atlas of Inflammatory Bowel Diseases - Kim, Won Ho; Cheon, Jae Hee (Springer Berlin Heidelberg : Imprint: Springer, 2015)
This comprehensive atlas, containing a wealth of high-quality images, illustrates the complete spectrum of presentations of inflammatory bowel diseases (IBD). It focuses especially on the most recent developments in the use of endoscopy in IBD, providing detailed guidance on endoscopic indices of disease activity, diagnosis, and differential diagnosis. In addition to ileocolonoscopy, small bowel endoscopy, and esophagogastroduodenoscopy, chapters are included on the role of both established radiological techniques, such as CT, MRI, and abdominal ultrasonography, and the newest approaches, including high-resolution endoscopy, narrow band imaging, and confocal laser endomicroscopy. Extraintestinal manifestations and complications are addressed in separate chapters, and the book concludes by presenting surgical findings. The authors are international authorities with diverse expert knowledge who have collaborated to create an ideal tool for all who wish to master endoscopic evaluation in IBD.